Meta-analysis of delayed gastric emptying after pylorus-preserving versus pylorus-resecting pancreatoduodenectomy - Klaiber, Ulla; Probst, Pascal; Strobel, Oliver; Michalski, Christoph; Dörr-Harim, Colette; Diener, Markus K.; Büchler, Markus W.; Hackert, Thilo (The British journal of surgery, 2018)
Delayed gastric emptying (DGE) is a frequent complication after pylorus-preserving pancreatoduodenectomy. Recent studies have suggested that resection of the pylorus is associated with decreased rates of DGE. However, superiority of pylorus-resecting pancreatoduodenectomy was not shown in a recent RCT. This meta-analysis summarized evidence of the effectiveness and safety of pylorus-preserving compared with pylorus-resecting pancreatoduodenectomy.
Gesehen am 25.10.2019